2011
DOI: 10.1016/j.intimp.2011.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anti-phencyclidine monoclonal antibody therapy decreases phencyclidine-induced in utero fetal mortality in pregnant rats

Abstract: Illicit drug use during pregnancy is a serious social and public health problem inflicting an array of deleterious effects on both mother and offspring. We investigated the hypothesis that a murine anti-phencyclidine (PCP) monoclonal antibody (mAb6B5; KD=1.3 nM) can safely protect mother and fetus from PCP-induced adverse health effects in pregnant rats. Pregnant Sprague-Dawley rats (n=4–5) were intravenously administered bolus injections of PCP (1 mg/kg) on multiple days during pregnancy. They were also chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…This could indicate a slow leakage or transport of mAb4G9 into the fetal compartment. This interpretation is also based on similar studies testing the effects of anti-PCP mAb6B5 on PCP disposition in late-stage pregnant rats and their fetuses (Hubbard et al, 2011a) and results from other studies (Arizono et al, 1994;Nekhayeva et al, 2005).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This could indicate a slow leakage or transport of mAb4G9 into the fetal compartment. This interpretation is also based on similar studies testing the effects of anti-PCP mAb6B5 on PCP disposition in late-stage pregnant rats and their fetuses (Hubbard et al, 2011a) and results from other studies (Arizono et al, 1994;Nekhayeva et al, 2005).…”
Section: Discussionmentioning
confidence: 61%
“…Therapeutic and safety endpoints show mAb6B5 treatment produces significant reductions in maternal and fetal PCP brain concentrations. These data also show mAb6B5 treatment does not adversely affect maternal weight gain, pup birth weights, pregnancy outcome, or fetal growth; and, more importantly, mAb6B5 substantially reduces PCPinduced fetal deaths (Hubbard et al, 2011a).…”
Section: Introductionmentioning
confidence: 55%
“…Passive immunization with anti-6-AM mAb dose dependently reduced heroin-induced psychomotor activation and brain levels of 6-AM and morphine in adult male mice (Bogen et al, 2014;Kvello et al, 2016). While maternal immunization for fetal protection against nicotine, methamphetamine, and phencyclidine has been investigated in rats (Keyler et al, 2003(Keyler et al, , 2005Hubbard et al, 2011a;White et al, 2014), maternal immunization against heroin has not been reported previously. Furthermore, former studies have primarily assessed materno-fetal drug distribution, whereas immunotherapeutic protection against long-term effects of prenatal drug exposure has not been explored.…”
Section: Introductionmentioning
confidence: 99%